HACIA UNA SOCIEDAD DE LA INFORMACIÓN EQUITATIVA Y SOLIDARIA - Freyre Valladolid, Mayela (2005)
The dramatical changes that are taking place in technologies of communication have meant the damage of paradigms in the current society. The new society of information requires a new vision different from the ones that have brought economical, social and political inequity to our population, reflected on the growing poverty and exclusion. In this context, the so called «digital breach» is one of the most evident manifestations of the social exclusion that has to be assisted immediately.